Utility Estimation of a Set of States of Health - Card, W. I.; Rusinkiewicz, M.; Phillips, C. I. (Methods of Information in Medicine, 1977)
A decision maker was presented with three states of health, such that an imaginary patient was in the middle state while the two other states could be described as more preferred and less preferred. The decision maker was then asked to choose the minimal odds at which he would advise an operation which would result in success, the patient moving into the more preferred state, or failure, the patient moving into the less preferred state. Eight decision makers were tested in this way and each made 24 such wagers on a set of three states chosen from a total set of eight; each of these states differed unidimen sionally only in the visual acuity of the remaining eye in the imaginary patient. If the utility of I is arbitrarily assigned to the state of perfect vision, and the utility of 0 to the state of non-perception of light, estimates of the utilities of the intervening states can then be made. The utility function for each decision maker was constructed and was found to be linear against the logarithm of the visual acuity. From this it follows that if all decision makers, e.g. ophthalmic surgeons, show such linearity, they will all choose the same odds before deciding whether to operate and these odds are independent of the utilities which the individual decision maker attaches to the different states of health.
Keywords: Decision Making; Visual Acuity; Therapy; Utility Theory